2020
DOI: 10.1016/j.amsu.2020.08.002
|View full text |Cite|
|
Sign up to set email alerts
|

Do your surgical glove characteristics and wearing habits affect your tactile sensibility?

Abstract: Backround Tactile sensibility plays a critical role in medicine, especially in surgical practice. In order to prevent surgical site infections and protect the surgeon, the use of surgical gloves is standard practice. However, wearing these might affect the sensibility of the hand disadvantageously, especially in disciplines that require precision work. Methods We evaluated the influence of six different glove types, as well as gloves wearing habits (double gloving, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…Concerning effects of poor-fitting gloves, Moog et al 4 found that oversized gloves caused significantly deteriorated tactile sensibility. Undersized gloves did not affect sensibility but caused discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning effects of poor-fitting gloves, Moog et al 4 found that oversized gloves caused significantly deteriorated tactile sensibility. Undersized gloves did not affect sensibility but caused discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…The finger's interaction with a surface is physiologically detected by mechanoreceptors located at different levels in the skin [ 2 ]. Wearing gloves reduces the effectiveness of fine touch discrimination [ 3 ], although it is an indispensable protective barrier against bloodborne pathogens while performing surgery [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that evaluated the effect of medical gloves using standardized sensibility tests, i.e., Semmes-Weinstein monofilament and two-point discrimination, have shown that wearing gloves reduces significantly touch sensitivity [ 3 , 5 , 6 ]. To alleviate the impediment to surgical performance caused by gloves, surgeons have different glove wearing habits and preferences, i.e., personal choice of glove brand, glove thickness, single-gloving, double-gloving, well-fitted, undersized or oversized gloves [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sci. 2021, 11, 8294 2 of 14 hand [25][26][27][28]. In addition, the structure of the glove could hamper fingers' movements.…”
Section: Introductionmentioning
confidence: 99%